Epidemiological Characteristics and Causes of End-stage Renal Disease in Hemodialysis Patients - Mehdi Khazaei; Zainab Eslami Hasan Abadi; Mohammad Keshvari Delavar; Morteza Shamsizadeh (Shahrekord University of Medical Sciences, 2020)
Background and aims: Hemodialysis (HD) is considered as the main method of renal replacement therapy (RRT) for end-stage renal disease (ESRD) patients in many countries including Iran. Given the limited number of epidemiological studies in this regard at the provincial level across the country, the present study aimed to describe the demographic and clinical characteristics of ESRD patients and determine the most important causes of ESRD in Hamadan Province. Methods: This cross-sectional study was conducted on 508 HD patients in Hamadan province in January 2017. The checklist used to gather information comprised of the patient's demographic and clinical information. The analysis was carried out using descriptive analysis including frequency tables and charts and the chi-square statistic test was used to compare the groups using Stata software, version 12. Results: The prevalence rate of HD treatment was 288.9 per million population (PMP). Further, most under HD patients were married, illiterate, and urban residents. The mean age of patients at the diagnosis was 47.64 ± 15.17 years. Hypertension (37.4%), diabetes (28.74%), and glomerulonephritis (10.63%) were the common causes of ESRD. Eventually, there was a significant difference between ESRD causes according to gender and residency (P<0.05). Conclusion: In general, the prevalence rate of HD in Hamadan was relatively similar to that of developing countries although it was lower than the national average. Furthermore, hypertension and diabetes were the common causes of ESRD in Hamadan Province. Therefore, preventive strategies should be taken to modify their risk factors.